Influence of Spatial Abilities on Spatial Data Quality in Participatory Mapping - Yoga Kencana Nugraha; Purnama Budi Santosa (Indonesian Journal of Geography, 2022)
Participatory mapping (PM) method has become an alternative in spatial data collection activities for various mapping activities, including updating data on Rural & Urban Land and Building Tax (PBB-P2). From several experiences in PM application, various quality results have been found. Differences in the levels of spatial abilities of PM actors are assumed to affect the quality levels of PM results. Therefore, this study aimed to determine the effects of spatial abilities on the quality of spatial data generated in PM activities. It consisted of several stages of preparing instruments for measuring spatial abilities, collecting spatial data through PM, and correlation analysis. The instrument used to measure the levels of spatial abilities of 28 subvillage chiefs was the Purdue Spatial Visualization Test. The quality of PBB-P2 spatial data in 28 subvillages was randomly selected and assessed in terms of position, area, and geometric accuracies with reference to the land registration map from National Land Agency. Results indicated a positive correlation between the visual spatial ability and the spatial data quality of the PM results with a value of r = 0.823. Our findings are expected to be used as references for parties who carry out PM activities to be able to plan such activities.